INTERMITTENT FASTING IN NALFD: LIGHTENING AT THE END OF TUNNEL - Khan, Jibran Umar Ayub; Zahir Shah, Azhar; Qaisar, Ayesha; Abdul Wahab (Khyber Journal of Medical Sciences, 2023)
Non Alcoholic Fatty Liver Disease has been the cornerstone of hepatology diseases for the last so many years. 1It’s an incidental finding on routine scans done for different symptoms such as epigastric pain, jaundice,deranged liver function tests, constipation and even weight loss.2The consequence of NALFD and NASH to full blown cirrhosis and even hepatocellular cancer has shaken experts across the world to a colossal extent and they are puzzled about what should be the best course of action for it as it seems a benign disease with mere fat infiltration in the liver. 3Obesity has been found as the major culprit for it beside others such as diabetes and hypertriglycermia being components of metabolic syndrome which has own share of complications. 4 There are a large no of treatments which have been under trial for NAFLD.One of the drugs which has been used traditionally as anti diabetic drug for decades and still as first line drug in hyperglyceremia. 5Its utility for inducing weight loss in obese people has been quite known but it has got own side effects including bothersome gastrointestinal side effects and even life threatening lactic acidosis with renal impairment .The other class of drugs called statins for lowering increased cholesterol levels but can lead to deranged liver function tests and myopathies. One of the effective modalities that is research proven and has revolutionised the management of Non Alcoholic Fatty Liver Disease is intermittent fasting with excellent effect on liver function beside hugely beneficial for body mass index (BMI).6 Obesity that has been linked to insulin resistance that is cardinal in leading to metabolic syndrome and type 2 diabetes .The combination of intermittent fasting and exercise have dramatically transformed the prospect of NALFD patients with studies reporting it to be more effective than aerobic exercise alone and vice versa .6